Anthropometric research of congenital auricular deformities for newborns. (3rd April 2019) - Zhao, Hui; Lin, Guanfeng; Seong, Yong Hae; Shi, Jin; Xu, Jing; Huang, Wenhua
Abstract: Objective: This study aimed to get the data of Neonatal auricle for helping pediatricians and obstetricians to make definite diagnosis and individualized treatment for newborn congenital auricular deformities in China. Methods: A total of 1500 newborns' ears were evaluated in this study. Six surface measurements were performed directly on the auricles of the subjects as follows: physiognomic ear length and breadth, morphological ear length and breadth, cephalo-auricular distance, and cephalo otic angle. Results: The incidence of neonatal auricular deformities in the Pearl River Delta area was 57.47% and the self-healing rate was 31.61% by the 30-day follow-up. There were significant differences between different types of auricular deformities (protruding ear, cup ear, lop ear, Stahl's ear, conchal crus, helical rim deformity, and composite deformity) and normal morphological differences of the auricle. Conclusions: Our findings suggested that individual differences in ear morphology are large and there were some differences between measurement data in our study and EarWell. Application of the EarWell system may lead to localized skin excoriations or breakdown as a result of mismatch with the ear. Therefore, early use of personalized ear molds produced by three-dimensional printing to determine if more deformed auricles may be corrected.